PENGELOLAAN HARA MIKRO ZN DALAM TANAH UNTUK MENINGKATKAN KUALITAS DAN PRODUKTIVITAS TANAMAN/Management of Micro Zink Nutrition in Soil to Improve Plant Quality and Productivity - Mirawanty Amin; Herlina N Salamba; Asnawi Asnawi (Jurnal Penelitian dan Pengembangan Pertanian, 2022)
Zinc (Zn) is a micronutrient that has an important role in various physiological and photosynthetic processes of plants. However the important role of Zn has not yet been concidered. This paper discussed the source of Zn and its availability in the soil, the important role of Zn in plants and strategies to overcome Zn deficiency in the soil. Zn has an important role in increasing crop production and yield quality. Zn nutrients in soil derived from parent material with an average content of 78 mg/kg. The low Zn level in the soil causes stunted plant and low crop yields. Zinc deficiency in plants resulted leaf chlorosis, necrotic spots on leaves, stunted plants, deformed and stunted leaves. Zn deficiency in soil can cause yield loss up to 40% without the appearance of leaf symptoms. Plants absorb Zn in the form of Zn2+. Soils in Indonesia have low Zn content so that production and quality of crops are low. Zn plays an important role in plant growth, gene expression, enzyme structure, photosynthesis, pollen development, sugar transformation, protein synthesis, membrane permeability, signal transduction and auxin metabolism, and increasing maturation of seeds and stems. The critical limit of soil Zn for most plants ranges from 0.5-2.0 mg Zn/kg for DTPA extractant, while the critical limit in plant tissue is 20 mg Zn/kg. The management of Zn nutrients needs to be considered, although it is needed only in small amounts. Without Zn nutrient management, its concentration in soil will continuously decreased. Management strategies in overcoming low Zn availability in plants are application of fertilizer containing Zn and the use of varieties that have high Zn content. The application of ZnSO4 of 60 kg/ha can increased the yield of grain, straw, number of tillers, plant height and weight of 1000 grains in rice plants. The treatment of soaking rice seeds in a solution of 0.05% ZnSO4 for ± 5 minutes + 100 kg TSP/ha was the best treatment giving the highest grain weight in Grumusol and Alluvial.Keywords: Micronutrients Zn, deficiency, management AbtrakHara mikro Zn memiliki peranan penting dalam berbagai proses fisiologis dan fotosintesis untuk meningkatkan pertumbuhan dan hasil tanaman, namun belum mendapatkan perhatian. Naskah ini membahas sumber Zn dan ketersediannnya pada tanah, peranan penting hara Zn pada tanaman, dan strategi mengatasi kekurangan Zn dalam tanah. Hara Zn dalam tanah berasal dari batuan bahan induk tanah dengan kandungan rata-rata 78 mg/kg. Kadar Zn yang rendah di tanah menyebabkan pertumbuhan tanaman terhambat dan hasil rendah. Kekurangan Zn pada tanaman menyebabkan klorosis dan bintik-bintik nekrotik pada daun, pertumbuhan kerdil, dan daun cacat. Pada tanah yang kekurangan Zn, tanaman dapat mengalami kehilangan hasil hingga 40% tanpa gejala pada daun. Tanaman menyerap Zn dalam bentuk Zn2+. Tanah di Indonesia memiliki kandungan Zn yang rendah sehingga produksi dan kualitas tanaman rendah. Zn berperan penting dalam pertumbuhan tanaman, ekspresi gen, struktur enzim, fotosintesis, perkembangan polen, transformasi gula, sintesis protein, permeabilitas membran, transduksi sinyal, metabolisme auksin, pematangan biji dan batang. Batas kritis Zn dalam tanah untuk sebagian besar tanaman berkisar antara 0,5-2,0 mg Zn/kg untuk pengekstrak DTPA, sedangkan batas kritis pada jaringan tanaman 20 mg Zn/kg. Meskipun diperlukan tanaman dalam jumlah yang kecil, hara Zn perlu dikelola dengan baik. Strategi pengelolaan hara Zn agar selalu tersedia di tanah adalah melalui pemupukan dan penggunaan varietas yang mengandung Zn tinggi. Pemberian ZnSO4 60 kg/ha dapat meningkatkan hasil gabah, jerami, jumlah anakan, tinggi tanaman, dan bobot 1.000 butir tanaman padi. Perlakuan perendaman bibit padi dalam larutan 0,05% ZnSO4 selama ± 5 menit + 100 kg TSP/ ha memberikan bobot gabah tertinggi pada Grumusol dan Aluvial.Kata kunci: Hara mikro Zn, defisiensi, pengelolaan